Long term effect of alpha interferon in children with chronic hepatitis B. Issue 5 (1st May 2000) - Bortolotti, F; Jara, P; Barbera, C; Gregorio, G V; Vegnente, A; Zancan, L; Hierro, L; Crivellaro, C; Vergani, G Mieli; Iorio, R; Pace, M; Con, P; et al.
Abstract : BACKGROUND/AIMS: The purpose of this study was to better define the long term prognosis of infection and disease in children with chronic hepatitis B treated with interferon (IFN) alpha. PATIENTS: A total of 107 children with chronic hepatitis B who received IFN alpha for three or six months in two clinical trials were followed for a mean period of 69 (17) months. Response to treatment was defined as loss of hepatitis B e antigen (HBeAg) within 12 months after stopping treatment. A control group of 59 patients was also followed for a shorter mean time (46 (19) months). RESULTS: Sixteen (15%) treated children responded during therapy and 18 (17%) during post-treatment follow up; 31 (29%) non-responders lost HBeAg during subsequent years. High pretreatment levels of transaminases and a greater histological activity index were predictors of response. Kaplan-Meier estimates of cumulative HBeAg clearance rates at five years were similar between treated patients (60%) and controls (65%). After HBeAg clearance, all cases lost hepatitis B virus DNA and 94% had normal transaminase levels. Loss of hepatitis B surface antigen (HBsAg) occurred in four (25%) patients who responded during treatment but in none of the other treated or untreated patients. CONCLUSIONS: After five years' observation, the proportion of treated children with sustained HBeAg clearance comprised an equal number of responders and non-responders and did not differ from that observed in untreated controls, suggesting that IFN simply accelerated a spontaneous event. However, IFN significantly improved the rate of HBsAg loss in cases with more prominent disease activity who were early responders, and may be particularly useful in this type of patient.